DNA methylation and mRNA expression of glutathione S-transferase alpha 4 are associated with intracranial aneurysms in a gender-dependent manner - Xu, Tianqi; Yu, Xi; Zhou, Shenjun; Wu, Yiwen; Deng, Xinpeng; Wu, Yuefei; Wang, Shiyi; Gao, Xiang; Nie, Sheng; Zhou, Chenhui; Sun, Jie; Huang, Yi (Frontiers in Genetics, 2023)
Objective: We performed a case-control study to investigate the correlation between DNA methylation and mRNA expression of the glutathione S-transferase alpha 4 (GSTA4) gene and the risk of intracranial aneurysm (IA) in the Chinese Han population. Methods: After propensity score matching, 44 pairs of cases and controls were collected in this study. Fasting blood samples were collected for DNA and RNA extraction within 24 h of admission. Nine CpG dinucleotides were selected from the GSTA4 promoter region for DNA methylation pyrosequencing. mRNA expression of GSTA4 was measured by quantitative real-time polymerase chain reaction (RT-qPCR). In vitro cell experiments were conducted to verify the association between 5-aza-2′-deoxycytidine induced DNA hypomethylation and GSTA4 mRNA expression. Results: The mean methylation level of GSTA4 was much lower in IA patients, especially in IA patients, especially in unruptured IA (UIA), than that in controls (IA vs. Control, p < .001; ruptured IA (RIA) vs. Control, p = .005; UIA vs. Control, p < .001). With sex stratification, we further found that the association between GSTA4 methylation and IA risk presented only in women (mean methylation level: IA vs. Control, p < .001; RIA vs. Control, p = .009; UIA vs. Control, p < .001). GSTA4 mRNA expression was significantly higher in the IA group than in the control group (p < .01) and negatively correlated with DNA methylation in all individuals (r = −.746, p < .001). DNA hypomethylation can increase GSTA4 mRNA expression in human primary artery smooth muscle cells. The receiver operating characteristic (ROC) curve showed that GSTA4 mean methylation (AUC = .80, p < .001) was a reliable predictor of women intracranial aneurysm, among which CpG 1 exhibited the best predictive value (AUC = .89, p < .001). In addition, GSTA4 expression levels could also predict the risk of IA in women (AUC = .87, p = .005). Conclusion: Decreased DNA methylation and increased mRNA expression of the GSTA4 gene are associated with the risk of IA in women.